(untitled) (Scottish Historical and Archaeological Internet Reports, 2023)
In 1995 small-scale excavations undertaken at Cramond, Edinburgh revealed a number of pit and post hole features related to temporary or intermittent Mesolithic occupation. These features and associated deposits produced sizeable assemblages of charred plant remains and lithic material. Cramond appears to be the first of an increasing number of securely dated narrow-blade microlithic sites excavated in recent times along the Forth Littoral. Together with substantial house sites such as Echline Fields, East Barns and Howick, Cramond produced a narrow-blade microlithic industry associated with occupation during the mid-9th millennium BC. As such it remains the earliest narrow-blade type assemblage yet discovered in Britain and provides a jumping off point for the discussion of Mesolithic responses to a rapidly changing environment in terms of population movement and technological change.